Mycorrhizal network: a bidirectional pathway between green-leaved terrestrial orchids and pine trees - Chen, Jianxin; Ma, Xiang; Wu, Fengjinglin; Qiao, Na; Xu, Xingliang; Wu, Jianrong (Frontiers in Plant Science, 2025)
IntroductionIncreasing evidence demonstrates that plant roots can be connected via mycorrhizal networks. Such networks in roots play key roles in plant physiology and ecosystem functioning, but it remains debated whether bidirectional transfers of resources can occur simultaneously inside the network.MethodsWe constructed a compartmented system to test for bidirectional carbon (C) and nitrogen (N) transfer between three terrestrial orchids (Cymbidium goeringii, C. goeringii var. serratum, and C. faberi) and Pinus yunnanensis seedlings, which were linked via a common Ceratobasidium sp. A 13C and 15N dual labelling approach was employed to trace the simultaneous movement of both elements.ResultsA unidirectional transfer of C and N was observed between C. goeringii and pine seedlings. In contrast, simultaneous bidirectional transfer of both elements occurred between the other two orchid species and pine seedlings; 1.0–3.7% of assimilated C and 0.20–12.2% of acquired N were transferred through the network. The net C transfer was consistently directed from pine seedlings to the orchids. Nitrogen transfer exhibited three distinct, species-specific patterns: (i) unidirectional from C. goeringii to pine, (ii) bidirectional with no net transfer between C. faberi and pine, and (iii) bidirectional with a net transfer from C. goeringii var. serratum to pine.DiscussionThe divergent transfer patterns among orchid species demonstrate that mycorrhizal networks function as dynamic, species-specific pathways for resource transfer. This specificity may significantly influence orchid recruitment and nutrient dynamics in forest understories, suggesting that the role of common mycorrhizal networks is more complex than previously recognized.